SEASONAL DYNAMICS OF SOIL CILIATES OF SAMUR-YALAMA NATIONAL PARK - I. Kh. Alekperov; V. F. Mamedova (Юг России: экология, развитие, 2014)
Abstract. The article describes the seasonal dynamics, as well as a comparison of the species composition and structural analysis of communities of soil ciliates.Methods. Assembled with standard collection points soil samples delivered to the laboratory for further processing. Comparison of species composition of soil ciliates two different sites was carried out by Czekanowski-Sorensen, and to analyze the community structure of soil ciliates are normally used in environmental studies-dominance indices Simpson, Margalef species diversity.Results.Studies have shown that the species composition and abundance of soil ciliates individual species consistently changing seasons of the year. In general it can be noted that the total number of seasonal dynamics of soil ciliates is a bimodal curve with peaks in spring and autumn and minima in winter and summer.Main conclusions.Species composition and the total number of soil ciliates in the territory of the Samur-Yalama National Park varies both qualitatively and quantitatively depending on the time of year. Some regularities in the change of species of soil ciliates in forest soils Samur - Yalama National Park. Studies have shown the presence of certain seasonal faunal assemblages in communities of soil ciliates. The qualitative and quantitative distribution of ciliates pedobiontov affect environmental factors (both abiotic and biotic) causing microzonation distribution of these free-celled animals within a few centimeters.